A Thermally Activated Delayed Fluorescence Emitter Investigated by Time‐Resolved Near‐Infrared Spectroscopy. Issue 2 (17th November 2022) - Haselbach, Wiebke; Kaminski, Jeremy M.; Kloeters, Laura N.; Müller, Thomas J. J.; Weingart, Oliver; Marian, Christel M.; Gilch, Peter; Nogueira de Faria, Barbara E.
Abstract: Emitters for organic light‐emitting diodes (OLEDs) based on thermally activated delayed fluorescence (TADF) require small singlet (S1 )‐triplet (T1 ) energy gaps as well as fast intersystem crossing (ISC) transitions. These transitions can be mediated by vibronic mixing with higher excited states S n and T n ( n =2, 3, 4, …). For a prototypical TADF emitter consisting of a triarylamine and a dicyanobenzene moiety (TAA‐DCN) it is shown that these higher states can be located energetically by time‐resolved near‐infrared (NIR) spectroscopy. Abstract : A metal‐free TADF (thermally activated delayed fluorescence) emitter was investigated by time‐resolved near‐infrared spectroscopy. This enabled upper excited states that contribute to spin‐vibronic coupling to be detected.